Konsep Pendidikan Karakter Sosial Berbasis Al-qur’an - Amelia Salamah. S (Kopertais Wilayah I DKI Jakarta dan Banten, 2021)
This research produces a social character education concept based on the Koran, and reveals a form of character education theory called social humanism, theomorphic character education theory, which is a theory that describes the existence of education for human social characters that cannot be separated from God's guidance in Al-Qur'an, namely educating human social character such as: 1. التدارج / do gradually which continues to increase continuously, 2. تعارف / know each other; 3. تفاهم / understand each other; 4. تعاون / participate each other; 5. تكافل / support each other; 6. تسامح / tolerance; 7. تام / positive thinking and humans are given the opportunity to follow it with all the consequences in every activity of life. In addition, this study also concludes that the essence of character education in Indonesia, especially in the 2013 education curriculum (kurtilas), is to educate religious character, love for the country, intellectuality, and reveal that it contains social characters. This research is equipped with an implementation model as a medium of delivery to students which is called the